UPLC-TOF-MS analysis of Galium spurium towards its neuroprotective and anticonvulsant activities - Orhan, Nilufer; Orhan, Didem Deliorman; Aslan, Mustafa; Sukuroglu, Murat; Orhan, Ilkay Erdogan (Elsevier Ireland Ltd, 2012)
Ethnopharmacological relevance: Galium species have been reported to be used against epilepsy in traditional Turkish folk medicine. Aim of study: The present work was undertaken to evaluate the in vivo anticonvulsant and in vitro neuroprotective effects of Galium spurium L and to determine the major constituents by UPLC-TOF-MS. Materials and methods: Anticonvulsant activity of the aerial parts of Galium spurium was investigated using pentylenetetrazole, picrotoxin, and maximal electroshock-induced seizure animal models. In order to evaluate the safety, neurotoxicity (Rota rod test) of the ethanol extract was also determined. In vitro neuroprotective effect of the ethanol extract of Galium spurium was assessed by acetylcholinesterase and butrylcholinesterase inhibitions. Ultra Performance Liquid Chromatography-Time of Flight Mass Spectrometer (UPLC-TOF-MS) was used to identify the major compounds in the extract. Results: In pentylenetetrazole-induced seizure, the ethanol extract at doses of 250 and 1000 mg/kg prolonged the onset of seizures. Similarly, Galium spurium (250 and 500 mg/kg) significantly delayed the onset of picrotoxin-induced seizures in mice and these doses also exhibited 12.5% and 17% protection, respectively, against picrotoxin-induced seizures. Furthermore, Galium spurium extract showed a significant protective effect against maximal electroshock-induced seizures at doses of 250 and 1000 mg/kg (50% and 37.5%, respectively) and also all tested doses prolonged the onset of seizures. No motor coordination was observed with intraperitoneal injection of Galium spurium extract at doses of 500 and 1000 mg/kg. The extract exhibited 16.2% inhibition against butrylcholinesterase at 200 mu g/mL concentration, whereas it did not inhibit acetylcholinesterase. Phytochemical analysis of the extract based on the MS data by UPLC-TOF-MS, ten major compounds (phenolic and triterpenic acids, flavonoids and iridoids) were determined. Conclusions: The results indicate that Galium spurium may have anticonvulsant activity against picrotoxin and maximal electroshock-induced seizures in mice. Phenolic acids, flavonoids and iridoids might be responsible for anticonvulsant activity. The results offer possible beneficial effects by the plant's aerial parts and may suggest a realistic explanation for its traditonal usage in epilepsy. (c) 2012 Elsevier Ireland Ltd. All rights reserved.
Keywords: Cholinesterase inhibition; Galium spurium; LC-TOF-MS; Maximum electroshock; Pentylenetetrazole; Picrotoxin